PENGARUH GOOD CORPORATE GOVERNANCE, KINERJA LINGKUNGAN DAN ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN - Fangbethia, Bella; Desmiyawati, Desmiyawati; Supriono, Supriono (Jurnal Kajian Akuntansi dan Auditing, 2025)
This study aims to examine the impact of good corporate governance, environmental performance, and enterprise risk management on firm value. Corporate governance is proxied by institutional ownership and the board of independent commissioners. The control variables include firm size and leverage. The population in this study includes all basic material companies listed on the IDX for the period 2021-2023. The sample was selected using purposive sampling method, a total of 30 companies. The data used in this study are secondary data obtained through annual reports of basic material companies for the period 2021-2023. The hypotheses are tested using linear regression, with the SPSS as the analysis tool. The research findings indicate that institutional ownership has a significant effect on firm value, while the board of independent commissioners has no effect. Similarly, environmental performance shows no significant impact on firm value, whereas enterprise risk management demonstrates a significant effect. The results of this study are expected to serve as a valuable consideration for companies in evaluating, improving, and enhancing their value.